PEMETAAN POTENSI BENCANA ALAM (GEO-DISASTER) AKIBAT PENAMBANGAN BIJIH TIMAH DI KECAMATAN JEBUS DAN PARIT TIGA, KABUPATEN BANGKA BARAT - S.T., M.Eng., Irvani,; Tono, S.T., E.P.S.B. Taman (Jurusan Teknik Pertambangan FT UBB, 2014)
The study area is a tin mining region in hundred years, located in Jebus and Parit Tiga District, West Bangka Regency, Bangka Belitung Archipelago Province. Identifying some geo-disaster potential, in order that the geo-disaster mapping caused by tin mining activity is done. The research is done by observing geological, geomorphological, erosion dan sedimentation conditions, mass movement, abrasion, dan floods. Geo-disaster potential is ilustratrated in map as result of work using geographic information system (GIS) software. Geo-disasters that come from tin mining at study area are erosion, sedimentation, mass movement, floods and abrasion on the beach, which is about 67% area.Keywords: Geo-disaster, Mapping, Mining, Potential.